1996
DOI: 10.1097/00001648-199609000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic Lateral Sclerosis after Long-Term Exposure to Drinking Water with High Selenium Content

Abstract: We evaluated the risk of Wilms' tumor in the offspring of women taking various medications during pregnancy in a case, control study conducted in Brazil. The study accrued 109 cases and 218 age- and gender-matched hospital controls. After adjustment for known confounders, we found a strong association with ingestion of dipyrone (odds ratio = 10.9; 95% confidence interval = 2.4-50) particularly in women from low-income families. Although dipyrone-containing analgesics are banned in Europe and North America, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(24 citation statements)
references
References 0 publications
0
22
0
1
Order By: Relevance
“…The potential involvement of genetic and environment exposures in the development of WT is challenge to be explored, because in WT both genetic and environmental component are involved, although the exact aetiology remains unclear [23,24]. In a small case-control study conducted in different Brazilian cities, positive associations among parental exposure to pesticides before birth and maternal exposure to dipyrone during pregnancy were observed [25,26]. An elegant ecological analysis described by McNally et al suggested that environmental exposure and life style are associated with WT and soft tissue sarcomas [27].…”
Section: Discussionmentioning
confidence: 99%
“…The potential involvement of genetic and environment exposures in the development of WT is challenge to be explored, because in WT both genetic and environmental component are involved, although the exact aetiology remains unclear [23,24]. In a small case-control study conducted in different Brazilian cities, positive associations among parental exposure to pesticides before birth and maternal exposure to dipyrone during pregnancy were observed [25,26]. An elegant ecological analysis described by McNally et al suggested that environmental exposure and life style are associated with WT and soft tissue sarcomas [27].…”
Section: Discussionmentioning
confidence: 99%
“…Adequate dietary supplementation of Se is thought to prevent cancer. In contrast, chronic Se intoxication has been reported in areas with high levels of Se in the soil (11)(12)(13). Acute Se intoxication is very rare, perhaps due to the discomfort or incompatibility with normal living conditions associated with the extremely strong garlicky odors that ingestion causes.…”
Section: Discussionmentioning
confidence: 99%
“…Vinceti et al [46] studied a population that was also exposed to high levels of environmental selenium in Rivalta, Italy, where the municipal tap water contained elevated levels of selenium between 1972 and 1988. A cohort of residence living in Rivalta between 1980 and 1985 were found to have a standardized incidence ratio of 4.22 (95% CI: 1.15-10.8) compared to the unexposed population of the municipality.…”
Section: Seleniummentioning
confidence: 99%